A project guide to UX design : for user experience designers in the field or in the making - Unger, Russ (Voices that matter., 2009)
"This book presents a chapter-by-chapter guide through an appropriate User Experience process, as well as provides additional information on the creating SOWs and Proposals, Project Ecosystem, best practices for meetings, and understanding business requirements. User Experience neophytes and professionals alike should be able to find information relevant to any phase of a project in this book"--Resource description page